Guidelines for the prevention and management of Mycobacterium tuberculosis infection and disease in adult patients with chronic kidney disease. Issue 6 (3rd June 2010) - ,; Milburn, Heather; Ashman, Neil; Davies, Peter; Doffman, Sarah; Drobniewski, Francis; Khoo, Saye; Ormerod, Peter; Ostermann, Marlies; Snelson, Catherine
Abstract : Guidelines have been compiled by the Joint Tuberculosis Committee of the British Thoracic Society for the prevention and management of Mycobacterium tuberculosis infection and disease in patients with all grades of renal impairment.